hubungan pola asuh orang tua dengan masalah mental emosional remaja - ulfi mardhiah (Jurnal Medika Hutama, 2022)
purpose : to determine whether there is a relationship between parenting and adolescent mental emotional problems. method : this study was a descriptive correlation with a cross sectional approach. The research sample consisted of 30 respondents who were taken through accidental sampling technique. The measuring instruments used are Parental Authory Questionnaire (PAQ) for parenting style variables and Self-Reporting Questionnaire (SRQ) for mental emotional problems variables. result : The study showed that there was a relationship between parenting styles with adolescent mental emotional problems with p value (0.00) < α (0.05). There is a relationship between parenting styles and adolescent mental emotional problems in Asam Kumbang village, Pesisir Selatan district. Based on this research, usually parents tend to use all parenting styles. But there is only one dominant parenting style that parents always apply. conclution : after doing research on the relationship between parenting styles and adolescent mental emotional problems in Asam Kumbang village, the result is the majority of respondent aged is 18 years old , the majority the gender is female , the order of sequence is middle and yongest child and the majority education level is high school. democratic parenting is the most widely applied for parenting in Asam Kumbang village , while mental emotional problem were only 10 respondent.